Everyday finance : economics, personal money management, and entrepreneurship. (Gale virtual reference library, 2008)
Provides basic and practical information on economics, personal money management, and starting a business. Explains the foundations of economic theories; shows how various financial institutions and the stock market work; sheds light on social security; examines basic business and accounting practices; and demonstrates how to manage and make money in everyday life.